Association of salivary retinol-binding protein 4 levels with periodontal disease in obese and nonobese individuals: A case–control study - Mohamed Thaha; Arvina Rajasekar (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Periodontitis is an inflammatory infectious disease influenced by systemic inflammation, with obesity playing a key role in affecting human health and well-being. Retinol-binding protein 4 (RBP4), an adipokine elevated in obesity, is involved in inflammatory signaling and may serve as a biomarker for periodontal disease. While previous studies assessed serum RBP4, saliva offers a noninvasive, site-specific medium. Evaluating salivary RBP4 may provide insights into periodontal medicine and obesity-associated inflammation. Purpose: To evaluate and compare salivary RBP4 levels in obese and nonobese individuals and examine their relationship with clinical periodontal indicators. Methods: This cross-sectional, case-control study consisted of 50 systemically healthy individuals (25 obese and 25 nonobese), aged 25–50 years. Probing pocket depth (PPD) and clinical attachment level (CAL) were assessed. Unstimulated saliva samples were obtained, and RBP4 levels were determined via enzyme-linked immunosorbent assay. Statistical analyses involved independent t-tests and Pearson’s correlation. Results: Obese individuals showed substantially higher mean PPD (6.46 ± 1.02 mm), CAL (7.97 ± 1.46 mm), and salivary RBP4 concentration (24.18 ± 2.54 ng/mL) compared with their nonobese counterparts (PPD: 3.72 ± 0.12 mm; CAL: 4.02 ± 0.02 mm; RBP4: 9.26 ± 1.62 ng/mL) (p < 0.05). A strong, statistically significant correlation was found between RBP4 levels and both PPD and CAL in both groups (p < 0.05). Conclusion: Salivary RBP4 concentrations were elevated in obese individuals, with a strong correlation to periodontal clinical indices. These findings suggest that salivary RBP4 may have potential as a noninvasive indicator of inflammatory activity in obesity-associated periodontal disease, warranting further investigation in larger, longitudinal studies.